Comparative Study of Reasons for Divorce Based on National Marriage Laws in Indonesia and Turkiye - Syifa, Siti Nur; Izzuddin, Ahmad (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2024)
Marriage aims to build a happy and eternal family, but realizing this is challenging because many factors trigger a conflict that leads to divorce. Research focuses on reasons for divorce based on marriage law. To sharpen reasoning in studying the laws of other countries, the research was carried out using comparison. The country chosen to compare with Indonesia is Turkey because Turkey has reformed family law in the form of a law, apart from that because Indonesia and Turkey have a majority Muslim population with a majority of the Shafi'i school of thought in Indonesia and Hanafi in Turkey. The research method uses a statutory and comparative approach with secondary data, namely Law Number 1 of 1974 concerning Marriage, the Compilation of Islamic Law (KHI), and the Turkish Civil Code 1926. The analysis uses three paths with conclusions based on vertical comparisons: Indonesia and the Islamic School of Religion. Shafi’i and Turkey, with the Hanafi School, both adopted some of the provisions of the school to become part of the regulations. Horizontally, the reasons for divorce in the Marriage Law in Indonesia and The Turkish Civil Code 1926 in Turkey are largely similar, and diagonally with a comparison of the history of marriage legislation, namely that every aspect of marriage law regulations is more or less influenced by the school of thought followed by that country.